2014
DOI: 10.15407/ubj86.04.119
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of fibrin polymerization by synthetic peptides corresponding to Аα195-205 and γ69-77 sites sites of fibrin molecule

Abstract: InhIbItIon of fIbrIn polymerIzatIon

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Thus, using small peptides, was discovered the important role of the hinge sites of the coiled-coil region of the fibrin(ogen) molecule in the process of fibrin polymerization. It has been demonstrated that synthetic peptide А195-205 inhibits the stage of fibrin protofibril formation, while peptide 69-77 inhibits the lateral association of protofibrils [7]. The use of small molecules helps minimize steric constraints that may arise from their binding to the fibrin(ogen) molecule.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, using small peptides, was discovered the important role of the hinge sites of the coiled-coil region of the fibrin(ogen) molecule in the process of fibrin polymerization. It has been demonstrated that synthetic peptide А195-205 inhibits the stage of fibrin protofibril formation, while peptide 69-77 inhibits the lateral association of protofibrils [7]. The use of small molecules helps minimize steric constraints that may arise from their binding to the fibrin(ogen) molecule.…”
mentioning
confidence: 99%
“…Scheme of fibrinogen molecule with some effectors (antibody, protease, peptide) targeted to the distinct parts of the molecule. Modified after: [13] I-3C antibody targeted to 122-134 residue of B-chain of fibrinogen[14]; BK134-G135 is a peptide bond that is cleaved during the formation of TSK-fragment of fibrinogen[15]; B125-135 is a synthetic peptide [16]; I-5A antibody targeted to 509-610 residue of A-chain of fibrinogen[17]; AA504-S505 -is a peptide bond that is cleaved by protease II from the culture medium of Bacillus thuringiensis[18]; AA414-610 is a peptide generated by protease from the venom of Gloydius halys halys[19]; I-3B antibody targeted to 15-53 residue of B-chain of fibrinogen[20]; BR42-A43 is a peptide bond that is cleaved by protease II from the venom of Echis multisquamatis[21]; B15-118 is a synthetic peptide[22]; II-4d antibody targeted to 86-240 residue of -chain of fibrinogen[23]; 69-77 is a synthetic peptide[7]; III-3B antibody targeted to 155-160 residue of B-chain of fibrinogen[24].…”
mentioning
confidence: 99%